2008
DOI: 10.1016/j.susc.2008.06.004
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of oxygen and hydrogen on Pd(111) surface

Abstract: The coadsorption and interactions of oxygen and hydrogen on Pd(111) was studied by scanning tunneling microscopy and density functional theory calculations. In the absence of hydrogen oxygen forms a (2×2) ordered structure. Coadsorption of hydrogen leads to a structural transformation from the (2×2) to a (√3×√3)R30 o structure. In addition to this transformation, hydrogen enhances the mobility of oxygen. To explain these observations, the interaction of oxygen and hydrogen on Pd(111) was studied within the den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
3
7
0
Order By: Relevance
“…We examined this possibility by carrying out DFT calculations on a model Pd(111) surface (representative of dominant facets on Pd NPs; fig. S1) with coadsorbed H*-and O*-atom coverages that were consistent with operando extended x-ray absorption fine structure (EXAFS) measurements (see below) and established adlayer structures (supplementary text, sections S3 and S4) (27). Ab initio molecular dynamics simulations were performed with liquid methanol on these covered Pd surfaces to generate the lowest-energy hydrogen-bonding networks over the catalysts and the adsorbates.…”
supporting
confidence: 65%
“…We examined this possibility by carrying out DFT calculations on a model Pd(111) surface (representative of dominant facets on Pd NPs; fig. S1) with coadsorbed H*-and O*-atom coverages that were consistent with operando extended x-ray absorption fine structure (EXAFS) measurements (see below) and established adlayer structures (supplementary text, sections S3 and S4) (27). Ab initio molecular dynamics simulations were performed with liquid methanol on these covered Pd surfaces to generate the lowest-energy hydrogen-bonding networks over the catalysts and the adsorbates.…”
supporting
confidence: 65%
“…On the other hand, the reaction of 2H­(a) + O­(a) → H 2 O­(a) on Pd already proceeds at ∼220 K. , The high reactivity of D­(a) is still kept, even in the presence of O­(a), N­(a), CO­(a), and NO­(a), because of the fast diffusion and a small activation barrier for the reaction with O­(a), around 29 kJ/mol . Thus, this reaction can control the coverage of D­(a) and O­(a); i.e., only either Θ O ≫ Θ D or Θ O ≪ Θ D is possible in the steady-state NO + CO + D 2 reaction under a high vacuum.…”
Section: Discussionmentioning
confidence: 99%
“…Surface species mostly consist of NO(a) and N(a) on Pd(211) at T S = 450−490 K in the presence of a nearly equimolar mixture of NO and CO, although both molecules adsorb efficiently on the clean surface. 75,76 On this surface, NO is partly dissociated at these temperatures → N 2 O(a) is significant, and actually, these adsorbed species are copresent below 420 K. 19,20 On the other hand, the reaction of 2H(a) + O(a) → H 2 O(a) on Pd already proceeds at ∼220 K. 77,78 The high reactivity of D(a) is still kept, even in the presence of O(a), N(a), CO(a), and NO(a), because of the fast diffusion and a small activation barrier for the reaction with O(a), around 29 kJ/mol. 79 .…”
mentioning
confidence: 99%
“…7,12,13 The CO and H form compressed, segregated domains on the Pd surface, 7,12À14 and with increasing CO coverage, H is forced to desorb or absorb into subsurface Pd sites, depending on specific conditions. 7,12,13 In related works, Salmeron and coworkers observed the compression of O by H on Pd(111) 15,16 and demonstrated that the strain of this compression is relieved by H dissolution into the bulk. 16 CO and O are also known to form segregated domains on both Pd(111) 17 and Pt(111), 9 and CO was shown to compress O on these surfaces due to its stronger adsorption energy.…”
mentioning
confidence: 98%
“…Notably, although most of these investigations have been carried out in ultrahigh vacuum (UHV), several have been corroborated by high-pressure , or macroscale measurements and a few studies have been performed with high-pressure scanning tunneling microscopy (STM), ,, confirming that the effects of segregation have ramifications on reaction kinetics under catalytically relevant conditions. A number of reports have investigated the coadsorption of CO and H on Pd(111), and it has been shown that there are repulsive interactions between the species. ,, The CO and H form compressed, segregated domains on the Pd surface, , and with increasing CO coverage, H is forced to desorb or absorb into subsurface Pd sites, depending on specific conditions. ,, In related works, Salmeron and co-workers observed the compression of O by H on Pd(111) , and demonstrated that the strain of this compression is relieved by H dissolution into the bulk …”
mentioning
confidence: 99%